?Kimmeridgian-Tithonian shallow- water platform clasts from mass flows on top of the Vardar/Axios ophiolites - Kostaki, G.; Kilias, A.; Gawlick, H. J.; Schlagintweit, F. (Bulletin of the Geological Society of Greece, 2013)
The Late Jurassic to Early Cretaceous sedimentary succession of the Neochorouda Unit lies unconformably on top of the Oreokastro ophiolites of the Vardar/Axios “suture zone” in northern Greece. This succession consists of turbidites and mass flows and provides an upper limit for ophiolite emplacement. New biostratigraphic and microfacies analysis from the clasts in the mass flows were carried out for a better understanding of the Late Jurassic to Early Cretaceous geodynamic history. Microfacies and organism content prove the onset of Late Jurassic carbonate platforms on top of a Middle to Late Jurassic nappe stack striking from the Eastern Alps to the Hellenides. Middle to Late Jurassic nappe stacking towards WNW to NW followed late Early to Middle Jurassic intra-oceanic thrusting in the Western Vardar/Axios (= Neotethys) Ocean and subsequent ophiolite obduction onto the Pelagonian Units forming a thin-skinned orogen on the lower plate. After ophiolite emplacement Kimmeridgian- Tithonian carbonate platforms sealed widespread this tectonic event. Tithonian extension due to mountain uplift resulted in partial erosion of these platforms and new extensional basins were formed. Late Tithonian to earliest Cretaceous erosion of the uplifted nappe stack including the obducted ophiolites resulted in sediment supply into the newly formed basins also east of the Pelagonian Units.